Effect of the introduction of Co and Ce‐doping on NO oxidation over Cr‐based composite oxides. Issue 2 (19th January 2016) - Cao, Yan; Cai, Wei
Abstract: NO oxidation reaction was studied over a series of Ce–Co–Cr–O catalysts with different Co/Cr and various Ce doped prepared by sol–gel method to evaluate the correlation of their structural with catalytic performance. These catalysts were investigated in detail by means of X‐ray diffraction (XRD), Brunauer–Emmett–Teller surface area analysis (BET), high‐resolution transmission electron microscope (HR‐TEM), X‐ray photoelectron spectroscopy (XPS), H2 ‐temperature‐programmed reduction (H2 ‐TPR) and temperature‐programmed desorption (TPD). The results demonstrate that the concentration of Co 3+ is the key factor that influences the activity, and high Ce‐doped amount could well disperse the Co species. Hence Ce(3)–Co(3)–Cr(1) catalyst exhibits the higher activity for NO oxidation among all catalysts. The activation energy ( Ea ) are also calculated, and the results explain that the pre‐exponential factor value is important when Ea are close. © 2016 Curtin University of Technology and John Wiley & Sons, Ltd.